Youngism: Discrimination and Stereotypes - Vojtĕch Bartoš; Michal Bauer; Jana Cahlíková; Julie Chytilová (CESifo GmbH, 2024)
Preferences and beliefs about different age groups shape social, political, and economic outcomes. This paper provides strong evidence of "youngism", which refers to systematic bias in social preferences and unfavorable stereotypes against young adults. Among nationally representative samples from the United States and Czechia, we show that participants in both countries are substantially less pro-social in controlled allocation tasks towards young adults relative to other age groups. This preference bias is widespread, similar in size to discrimination against immigrants, and increases with age. Next, we show that young adults are perceived as more immoral, less helpful, less responsible, less hard-working, and enjoying easier lives than other age groups. Finally, we provide suggestive evidence that these unfavorable stereotypes about young adults feed into the preference bias.
Keywords: C93; D64; D91; J14; 330; inter-generational conflict; social preferences; discrimination; stereotypes; youngism